2018
DOI: 10.3389/fphar.2018.00316
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Erythropoietic Biomarkers in Response to Treatment With Erythropoietin in Belgrade Rats

Abstract: Recombinant human erythropoietin (rHuEPO) is used effectively in the treatment of various anemic disorders. Belgrade rat is a useful animal model of anemia caused by defect in iron utilization. The objective of the present study was to investigate the dynamics of erythropoietic biomarkers in Belgrade rats receiving rHuEPO. Pharmacokinetics of rHuEPO was evaluated in Belgrade rats and normal rats after intravenous administration of single doses of the drug (100 and 1350 IU/kg). Pharmacodynamic biomarkers includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The selection of response biomarker is very important for a bioassay. The biomarkers approach has been widely used for pharmacokinetic studies of high molecular weight compounds in vivo and in volunteers [33,34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The selection of response biomarker is very important for a bioassay. The biomarkers approach has been widely used for pharmacokinetic studies of high molecular weight compounds in vivo and in volunteers [33,34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…PK and PD Studies. The doses were selected based on approximately equivalent doses in humans (Krzyzanski et al, 2013;Nguyen et al, 2018). The study design was based on previous experiments (Ait-Oudhia et al, 2010b;Krzyzanski et al, 2013;Yan et al, 2013), as shown in Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the evidences point to the combination treatments causing apoptosis via a mechanism other than the caspase pathway. Since the activity of caspase-3 and-9 are promoted by the release of the caspase-activating cytochrome c from mitochondrial membrane depolarization, it is postulated that rHuEPO stabilized the mitochondrial membrane rHuEPO ( Nguyen et al, 2018 ), preventing the release of cytochrome c and up-regulation of caspases and activation of the caspase-dependent apoptotic pathway by tamoxifen. One of our earlier studies showed that 3D MCF-7 spheroids treatment with EPO alone reduced cell viability without caspases activation.…”
Section: Discussionmentioning
confidence: 99%